2016
DOI: 10.1177/0266666915587032
|View full text |Cite
|
Sign up to set email alerts
|

Is being satisfied enough? Well-being and IT post-adoption behavior

Abstract: Well-being has rarely been used to discuss the post-adoption behavior of information technology users. Currently, satisfaction is the primary predictor of user behavior in IT post-adoption research. We live in an age when social media, mobile devices, the Internet, and other information technologies have virtually fused with our lifestyles. In discussing post-adoption behavior, focusing only on satisfaction might no longer be satisfactory. We should consider other constructs that might capture additional post-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
18
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(21 citation statements)
references
References 93 publications
2
18
0
1
Order By: Relevance
“…Shi ve diğerlerinin (2013) 328 kişi ile yaptığı çalışmada görülmüştür ki SAS'ların kullanımı ile hem mutluluk hem de iyi oluş arasında ilişki vardır ve SAS'lar hem mutluluğu hem de iyi oluşu yordamaktadır. Ong ve Lin (2015)'in 297 öğrenci ile yaptığı çalışmada yüksek iyi oluşa sahip kişilerin Facebook kullanımını sürdürmeye devam ettikleri görülmekte, bunun yanında yaşam doyumuna göre iyi oluşun Facebook kullanımını sürdürmede daha etkili olduğu anlaşılmıştır. Kim ve Lee (2011)'nin çalışmasında ise Facebook'taki arkadaş sayısının iyi oluşu yordadığı hem de aralarında ilişki olduğu görülürken, SAS kullanımının algılanan sosyal desteği ve olumlu kendini sunmayı yordadığı da bulunmuştur.…”
Section: Veri Toplama Aracıunclassified
“…Shi ve diğerlerinin (2013) 328 kişi ile yaptığı çalışmada görülmüştür ki SAS'ların kullanımı ile hem mutluluk hem de iyi oluş arasında ilişki vardır ve SAS'lar hem mutluluğu hem de iyi oluşu yordamaktadır. Ong ve Lin (2015)'in 297 öğrenci ile yaptığı çalışmada yüksek iyi oluşa sahip kişilerin Facebook kullanımını sürdürmeye devam ettikleri görülmekte, bunun yanında yaşam doyumuna göre iyi oluşun Facebook kullanımını sürdürmede daha etkili olduğu anlaşılmıştır. Kim ve Lee (2011)'nin çalışmasında ise Facebook'taki arkadaş sayısının iyi oluşu yordadığı hem de aralarında ilişki olduğu görülürken, SAS kullanımının algılanan sosyal desteği ve olumlu kendini sunmayı yordadığı da bulunmuştur.…”
Section: Veri Toplama Aracıunclassified
“…Continuance intention has been the subject of substantial theoretical developments (Rahman et al., 2017) such as IS continuance (Almaghrabi et al., 2011; Amoroso and Chen, 2017; Han et al., 2018; Susanto et al., 2016; Tella and Olasina, 2014; Tiyar and Khoshsima, 2015) and post-adoption usage (Jia et al., 2016; Ong and Lin, 2016). Continuance intention reflects post adoption behaviour and intention of continue using an information system (Limayem and Cheung, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, the research by Ong and Lin (2015) showed that Facebook use has a valuable connection with life satisfaction. The following hypothesis has therefore been developed:…”
Section: Habitual Facebook Usage and Life Satisfactionmentioning
confidence: 87%